Penyelesaian Tindak Pidana Ringan Menurut Peraturan Kapolri Dalam Mewujudkan Restorative Justice (Studi Di Polresta Deli Serdang) - Porlen Hatorangan Sihotang (Iuris Studia: Jurnal Kajian Hukum, 2020)
Minor Crime is a criminal offense that is light or not dangerous. One of the handling of minor crimes can be done by promoting the concept of restorative justice. Restorative justice can be carried out at the level of criminal proceedings, one of which is at the Police level. There is a problem in the field regarding its application, even though a Perkap has been enacted, including at the Deli Serdang Police. This research is a normative juridical research which is derived from data from interviews with the Deli Serdang City Police and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research, it is understood that the regulation on the settlement of Tipiring can be seen from the authority of the police in Article 15 Paragraph (1) letter e of Law Number 2 of 2002 concerning Police, the Perkap regulation used for this is Perkap Number 6 of 2019 concerning Criminal Investigation, Perkap Number 7 of 2008 and Perkap Number 14 of 2012, the arrangement for the settlement of Tipiring in the process is confirmed by the Chief of Police Circular Number: SE / 8 / VII / 2018 concerning the Application of Restorative Justice in the settlement of minor crimes according to the previous Perkap must meet formal and material requirements first in accordance with Article 12 of PerKap Number 6 of 2019, until in essence the two parties agree to settle the minor crime referred to in a peaceful manner, and finally a letter of termination of investigation / investigation of the case will be issued on the grounds of restorative justice signed by the Head of Police. Deli Serdang. Obstacles to resolving Tipirng according to Perkap at the Deli Serdang Police can occur from the side of the legal community and obstacles from legal norms that have not been applied uniformly.